Graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance and preparation method thereof
By utilizing the unique structure and redox treatment of graphene nanoribbons in nanocomposite foaming materials, combined with supercritical fluid foaming technology, a reinforced interface polarization structure is formed, which solves the problem of nanofiller spacing increase caused by pore wall stretching, and significantly improves the material's wave absorption performance.
Patent Information
- Application Number
- CN202310031067.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-01-10
AI Technical Summary
During the preparation of foamed material, the tensile action of the hole walls leads to an increase in the spacing of the nanofillers, destroying the polarization structure of the filler interface and overlap network structure, thereby reducing the wave absorption performance.
By utilizing the sheet-like structure and fibrous structure of the graphene nanoribbon, combining redox to adjust the in-plane atomic defects of the graphene nanoribbon, and using supercritical fluid foaming technology, a graphene nanoribbon-graphene nanoribbon interface polarization structure is formed to enhance the polarization of the nanofiller interface in the pore wall.
The absorption performance of nanocomposite foamed materials is significantly improved, and the reflection loss and good impedance matching are shown in the Ku band, the effective absorption bandwidth is increased and the reflection loss is reduced.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer nano-composite foaming wave-absorbing materials, and relates to a graphene nano-ribbon nano-composite foaming material with excellent wave-absorbing performance and a preparation method thereof. Background Art
[0002] Polymer materials have many advantages such as light weight, flexibility, and corrosion resistance, so they are currently widely used in many fields. At the same time, carbon nanomaterials with different morphological structures, such as zero-dimensional (0D) carbon black (CB), one-dimensional (1D) carbon nanotubes (CNT) and two-dimensional (2D) graphene (GNS), are often added to polymer matrices as functional fillers, which can significantly improve the physical and chemical properties of polymer materials, and are widely used in smart sensing materials, electromagnetic shielding materials, dielectric energy storage materials, thermal conductive materials and anti-aging materials. On this basis, polymer nanocomposite foam materials prepared by supercritical fluid foaming technology can further improve the wave absorption performance of the material. This is mainly because the introduction of the air phase (relative dielectric constant of 1) can greatly improve the impedance matching performance of the nanocomposite material and weaken the reflection performance of electromagnetic waves at the air / material interface.
[0003] In recent years, researchers have conducted a lot of research on nano-composite foaming materials and found that in the process of preparing foaming materials, the stretching effect of the pore wall promotes the orientation of the nano-filler, but also causes the spacing of the nano-filler to increase, thereby destroying the filler interface polarization structure and overlapping network structure. Therefore, if the pore wall stretching can be used in the foaming process while avoiding the adverse effect of the wall stretching on the filler interface polarization structure, and enhancing the interface polarization effect of the nano-filler in the pore wall, it is very beneficial to improve the wave absorption performance of the nano-composite foaming material. However, there is no report on the relevant method at present, and the present invention is proposed to solve this problem. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art. The present invention provides a graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance and a preparation method thereof. The wave absorbing performance of the nanocomposite foam material is effectively improved by utilizing the characteristics of graphene nanoribbon (GNR) having both a sheet structure and a fibrous structure, and by regulating the in-plane atomic defects of the graphene nanoribbon by redox and the combined effect of supercritical fluid foaming.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0006] A graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, the nanocomposite foam material consists of a polymer matrix material, graphene nanoribbons and an air phase, the graphene nanoribbons have atomic defects, the air phase is uniformly distributed in the polymer matrix material to form pores with a closed-cell structure, and the graphene nanoribbons are distributed in the pore walls to form a graphene nanoribbon-graphene nanoribbon interface polarization structure; in the nanocomposite foam material, the mass content of the graphene nanoribbons is 15wt%-20wt%, and the volume percentage of the air phase is 20%-30%.
[0007] In the technical solution of the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, the carbon-oxygen atomic ratio of the graphene nanoribbon is preferably (12-15):1, the distance between defects of the graphene nanoribbon is preferably 16-17 nm, and the I D / I G The ratio is preferably 1.1 to 1.2.
[0008] In the above-mentioned technical solution of the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, the graphene nanoribbon has both a sheet structure and a fibrous structure. The length of the graphene nanoribbon is basically consistent with that of the existing carbon nanotube, and the width is wider than the diameter of the existing carbon nanotube. It is formed by opening the tubular structure of the carbon nanotube through oxidation, and then adjusting the functional group content and creating in-plane atomic defects through reduction.
[0009] Furthermore, in the technical solution of the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, the preparation method of the graphene nanoribbon comprises the following steps:
[0010] (1) dispersing carbon nanotubes in a sulfuric acid-phosphoric acid mixed acid, stirring for 1 to 2 hours under ice bath conditions, adding potassium permanganate, then heating to 60 to 70° C., stirring and reacting for 2 to 4 hours, cooling the resulting reaction solution to room temperature and pouring it into ice water containing hydrogen peroxide, leaving it to stand for 20 to 30 hours, discarding the supernatant, and dialyzing the resulting reaction slurry with deionized water until the pH value of the reaction slurry is 6 to 7, thereby obtaining graphene oxide nanoribbons;
[0011] In the sulfuric acid-phosphoric acid mixed acid, the volume ratio of sulfuric acid to phosphoric acid is (8.5-9.5):1; the usage ratio of carbon nanotubes to sulfuric acid-phosphoric acid mixed acid is 150-250 mL of sulfuric acid-phosphoric acid mixed acid per 1 g of carbon nanotubes; the usage of potassium permanganate is 5-6 times the mass of the carbon nanotubes;
[0012] (2) reacting the graphene oxide nanoribbon obtained in step (1) at 900-950° C. in an inert gas atmosphere for 1.5-2 h to obtain graphene nanoribbon.
[0013] In the technical scheme of the above-mentioned graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, in the step (2) of preparing the graphene nanoribbon, the temperature is preferably increased from room temperature to 900-950°C in an inert gas atmosphere at a heating rate of 4-6°C / min, and kept at 900-950°C for 1.5-2h to obtain the graphene nanoribbon.
[0014] In the technical solution of the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, in the step (1) of preparing the graphene nanoribbon, the volume percentage of hydrogen peroxide in the ice water containing hydrogen peroxide is 5% to 10%, and the temperature of the ice water containing hydrogen peroxide is 0 to 4°C.
[0015] In the technical solution of the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, the polymer matrix material is a thermoplastic polymer.
[0016] In the technical solution of the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, the graphene nanoribbon-graphene nanoribbon interface polarization structure refers to a structure formed by the ends of the graphene nanoribbons in the pore wall overlapping with the ends of the adjacent graphene nanoribbons.
[0017] The present application has experimentally confirmed that the above-mentioned graphene nanoribbon nanocomposite foam material with excellent wave absorption performance has low reflection loss and good impedance matching in the Ku band (12.4-18GHz). When the mass content of the graphene nanoribbon is 15wt% and the volume percentage of the air phase in the nanocomposite foam material is 22% to 23%, the effective absorption bandwidth is 2.8GHz, and the reflection loss of the electromagnetic wave with a frequency of 16.8GHz is as low as -54.1dB, and the corresponding impedance matching is close to 1.
[0018] The present invention also provides a method for preparing the above-mentioned graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, comprising the following steps:
[0019] (1) preparing a graphene nanoribbon / polymer nanocomposite material by a solution blending method, and hot-pressing the obtained graphene nanoribbon / polymer nanocomposite material to obtain a composite material formed body;
[0020] (2) using a supercritical fluid to swell the composite material formed body and release the pressure to foam to obtain a nano-composite foam material, during the cell growth process, the cell wall is subjected to a two-dimensional stretching effect, the graphene nanoribbons are oriented in the cell wall and form a graphene nanoribbon-graphene nanoribbon interface polarization structure; in this step, the swelling and foaming conditions are controlled so that the volume percentage of the air phase in the nano-composite foam material is 20% to 30%.
[0021] In the technical scheme of the above-mentioned preparation method, the method of using supercritical fluid to swell the composite material molded body and release pressure for foaming is: placing the composite material molded body in a high-pressure cavity, introducing a gas as a foaming agent into the high-pressure cavity, adjusting the temperature and pressure of the high-pressure cavity to convert the gas as a foaming agent into a supercritical fluid state, maintaining the above-mentioned temperature and pressure to swell the composite material molded body, then releasing pressure for foaming, cooling and shaping, and obtaining a nano-composite foamed material.
[0022] In the technical scheme of the above-mentioned preparation method, when a supercritical fluid is used to swell and release the pressure to foam the composite material molded body, the temperature range and pressure range of the high-pressure cavity can be determined by referring to the existing supercritical fluid foaming technology. At the same time, the influence of the temperature and pressure of the high-pressure cavity on the volume percentage of the air phase in the nano-composite foaming material must also be considered. The temperature and pressure of the high-pressure cavity are controlled to ensure that the volume percentage of the air phase in the nano-composite foaming material reaches 20% to 30%.
[0023] For example, for semi-crystalline polymer materials, the temperature of the high-pressure cavity can generally be controlled near the melting point of the semi-crystalline polymer materials, and for amorphous polymer materials, the temperature of the high-pressure cavity can generally be controlled below the glass transition temperature of the amorphous polymer materials. On this basis, it is also necessary to consider that the temperature and pressure of the high-pressure cavity have an effect on the volume percentage of the air phase in the prepared composite foam material by 20% to 30%. Combining these factors, the temperature and pressure of the high-pressure cavity can be determined.
[0024] In the technical solution of the above preparation method, the gas introduced into the high pressure cavity as a foaming agent may be CO 2 or N 2 .
[0025] In the technical scheme of the above-mentioned preparation method, the method for preparing the graphene nanoribbon / polymer nanocomposite material by solution blending method is as follows: dissolving the polymer in a solvent to form a polymer solution; fully dispersing the graphene nanoribbons in the solvent to obtain a graphene nanoribbon dispersion; the solvent for dissolving the polymer is the same as the solvent for dispersing the graphene nanoribbons; mixing the polymer solution with the graphene nanoribbon dispersion, stirring under heating conditions until the mixed solution turns into a viscous state, and then drying to obtain the graphene nanoribbon / polymer nanocomposite material.
[0026] Compared with the prior art, the technical solution provided by the present invention can produce the following beneficial technical effects:
[0027] 1. The present invention provides a graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, which is composed of a polymer matrix material, graphene nanoribbons and an air phase, wherein the graphene nanoribbons have in-plane atomic defects and a high carbon-oxygen atomic ratio, the air phase is uniformly distributed in the polymer matrix material to form pores with a closed-cell structure, and the graphene nanoribbons are distributed in the pore walls to form a graphene nanoribbon-graphene nanoribbon interface polarization structure; the mass content of the graphene nanoribbons in the nanocomposite foam material is 15wt% to 20wt%, and the volume percentage of the air phase is 20% to 30%. The present invention utilizes the characteristics of graphene nanoribbons (GNR) having both a sheet structure and a fibrous structure, and uses a thermal reduction method to construct an appropriate amount of in-plane atomic defects on the GNR and reduce the functional group content therein, and introduces an appropriate amount of air phase by controlling the content of the graphene nanoribbons and foaming, thereby enhancing the impedance matching of the material on the one hand, and inducing the orientation of the GNR in the pore wall on the other hand to strengthen the GNR-GNR interface polarization structure, while utilizing the solid-gas interface formed by a large amount of foaming to enhance the multiple reflection and scattering properties of the material, and combining the good electron dissipation and conductivity of the GNR prepared by the thermal reduction method, the wave absorbing ability of the nano composite foaming material is effectively enhanced.
[0028] 2. The present invention has experimentally confirmed that the nanocomposite foam material provided by the present invention has low reflection loss and good impedance matching in the Ku band (12.4-18GHz). When the mass content of the graphene nanoribbon is 15wt% and the volume percentage of the air phase in the nanocomposite foam material is 22% to 23%, the effective absorption bandwidth is 2.8GHz, the reflection loss of the electromagnetic wave with a frequency of 16.8GHz is as low as -54.1dB, and the corresponding impedance matching is close to 1.
[0029] 3. The present invention also provides a method for preparing the above-mentioned graphene nanoribbon nanocomposite foam material with excellent absorbing properties. The method provides a new idea and feasible industrial preparation method for the preparation of highly absorbing carbon-based nanocomposite materials. The method is simple to operate, green and environmentally friendly, and is conducive to the large-scale production of such materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Figures (a) and (b) are scanning electron microscope images of MWCNT and GNR-thermR. Figure 1 Figure (c) is a transmission electron microscope image of GNR-thermR. Figure 1 Figures (d), (e), and (f) are the XRD patterns, Raman spectra, and thermogravimetric analysis test results of MWCNT, GONR, GNR-ChemR, and GNR-ThermR, respectively. Figure 1 Figure (g) shows the in-plane defect distances of MWCNT, GONR, GNR-ChemR and GNR-ThermR. Figure 1 Figures (h) to (k) are XPS graphs of MWCNT, GONR, GNR-ChemR and GNR-ThermR.
[0031] Figure 2 Figures (a), (e), and (i) are schematic diagrams of the structures of MWCNT / PVDF, GNR-ThermR / PVDF, and GNP / PVDF nanocomposites, respectively. Figure 2 Figures (b) to (d), (f) to (h), and (j) to (l) are the reflection loss test results under different nanofiller contents (5wt%, 10wt% and 15wt%).
[0032] Figure 3 Figures (a) to (c) show the reflection loss and impedance matching of MWCNT / PVDF, GNR-ThermR / PVDF and GNP / PVDF nanocomposites (unfoamed) when the nanofiller content is 15wt%. Figure 3 Figures (d) to (f) are SEM images of the cross sections of MWCNT / PVDF, GNR-ThermR / PVDF and GNP / PVDF nanocomposite foam materials. Figure 3 Figures (a') to (c') show the reflection loss and impedance matching of MWCNT / PVDF, GNR-ThermR / PVDF and GNP / PVDF nanocomposite foam materials.
[0033] Figure 4 Figures (a) to (c) are schematic diagrams of the evolution of filler interface polarization of CNT, GNR and GNP during pore wall stretching.
[0034] Figure 5 Figures (a) to (c) are schematic diagrams of GNR-ThermR / PVDF nanocomposite foam materials and their wave absorption with different air phase volume percentages. Figure 5 Figures (d) to (i) show the reflection loss and impedance matching of GNR-ThermR / PVDF nanocomposite foam materials with different volume percentages of air phase. DETAILED DESCRIPTION
[0035] The following examples further illustrate the method of using two-dimensional fillers to promote the orientation of one-dimensional fillers in the pore walls of the foamed material. The following examples are only part of the embodiments of the present invention, not all of them. Based on the content and embodiments of the present invention, other implementation methods obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention.
[0036] In the following examples and comparative examples, polyvinylidene fluoride (PVDF) was produced by Arkema, model Kynar2800; carbon nanotubes (MWCNTs) were produced by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, specification TNGM5; graphene nanosheets (GNPs) were provided by NanoXplore; potassium permanganate, phosphoric acid, sulfuric acid and hydrogen peroxide were provided by Chengdu Cologne Chemical.
[0037] Example 1
[0038] In this embodiment, the graphene nanoribbons are prepared by thermal reduction method, and the steps are as follows:
[0039] (1) Dispersing carbon nanotubes (MWCNT) in sulfuric acid-phosphoric acid mixed acid, stirring for 1 hour under ice bath conditions, then adding potassium permanganate to the resulting mixed solution in multiple times (potassium permanganate is added to the mixed solution in multiple times within 30 minutes), then heating to 65° C. within 1 hour and stirring at 65° C. for 3 hours, cooling the resulting reaction solution to room temperature, pouring the reaction solution cooled to room temperature into ice water containing hydrogen peroxide, leaving it to stand for 24 hours, pouring out the supernatant, introducing the resulting reaction slurry into a dialysis tube, dialyzing the resulting reaction slurry with deionized water until the pH value of the reaction slurry is 6-7, removing the liquid phase, and obtaining graphene oxide nanoribbons (GONR).
[0040] In the sulfuric acid-phosphoric acid mixed acid, the volume ratio of sulfuric acid to phosphoric acid is 9:1; the usage ratio of MWCNT to sulfuric acid-phosphoric acid mixed acid is 200 mL of sulfuric acid-phosphoric acid mixed acid for every 1 g of MWCNT; and the usage amount of potassium permanganate is 5 times the mass of MWCNT.
[0041] (2) placing the GONR obtained in step (1) in an argon atmosphere, heating the temperature to 900° C. at a heating rate of 5° C. / min and maintaining the temperature at 900° C. for 2 h to perform a reduction reaction, thereby obtaining graphene nanoribbons, denoted as GNR-thermR.
[0042] Comparative Example 1
[0043] In this comparative example, graphene nanoribbons were prepared by chemical reduction method, and the steps were as follows:
[0044] (1) The same operation as step (1) of Example 1 was performed to prepare graphene oxide nanoribbons (GONR).
[0045] (2) adding the GONR obtained in step (1) to deionized water, then adding hydrazine hydrate, mixing thoroughly, heating to 90° C. and keeping at 90° C. for 2 h to perform a reduction reaction, thereby obtaining graphene nanoribbons, which are referred to as GNR-ChemR;
[0046] In this step, the usage ratio of GONR to deionized water is 500 mL of deionized water per 1 g of GONR, and the usage ratio of GONR to hydrazine hydrate is 5 mL of hydrazine hydrate per 1 g of GONR.
[0047] Example 2
[0048] In this example, the GNR-thermR and GNR-ChemR prepared in Example 1 and Comparative Example 1 were characterized.
[0049] (1) The surface of the raw material MWCNT and the GNR-thermR prepared in Example 1 was gold plated for 60 seconds and observed using a scanning electron microscope (SEM). The results are as follows: Figure 1 The GNR-thermR prepared in Example 1 was observed using a transmission electron microscope (TEM). Figure 1 As shown in Figure (c).
[0050] (2) The crystal structures of the raw material MWCNT, the intermediate product GONR, the GNR-ChemR prepared in Example 1, and the GNR-ThermR prepared in Comparative Example 1 were studied by wide-angle X-ray diffraction (WAXD). The results are as follows: Figure 1 As shown in Figure (d).
[0051] (3) Thermogravimetric analysis (TGA) was performed on the raw material MWCNT, the intermediate product GONR, the GNR-ChemR prepared in Example 1, and the GNR-ThermR prepared in Comparative Example 1 to evaluate the thermal decomposition temperatures of MWCNT, GONR, GNR-ChemR, and GNR-ThermR. The test conditions were: 2 The temperature was raised from 50°C to 900°C at a heating rate of 10°C / min in the atmosphere. Figure 1 As shown in Figure (f).
[0052] (4) Raman spectroscopy was performed on the raw material MWCNT, the intermediate product GONR, the GNR-ChemR prepared in Example 1, and the GNR-ThermR prepared in Comparative Example 1. The results are as follows: Figure 1 The in-plane defect distances of MWCNT, GONR, GNR-ChemR and GNR-ThermR were characterized using 532nm excitation light. Figure 1 As shown in Figure (g).
[0053] (5) The surface element contents of the raw material MWCNT, the intermediate product GONR, the GNR-ChemR prepared in Example 1 and the GNR-ThermR prepared in Comparative Example 1 were tested using an X-ray photoelectron spectrometer (XPS). The results are shown in Figures (h) to (k) of the figure.
[0054] The relevant experimental parameters extracted from XRD, Raman and XPS spectra are shown in Table 1.
[0055] Table 1
[0056]
[0057]
[0058] Depend on Figure 1 As shown in Figures (a) to (c), MWCNT successfully opened its tubular structure during the oxidation process. Figure 1 As can be seen from Figure (d), after the oxidation process, the relative intensity of the 2θ peak dropped significantly from 100% of MWCNT to 19.7% of GONR (calculated based on the 2θ peak intensity of MWCNT), which means that the multilayer graphene structure of MWCNT was destroyed during the oxidation process; after the reduction process, the 2θ peak intensity of GNR-ChemR and GNR-ThermR increased slightly, which were 30.8% and 46.2%, respectively (calculated based on the 2θ peak intensity of MWCNT), which was mainly due to the stacking of graphene nanoribbons GNR (GNR-ChemR and GNR-ThermR) due to the reduction of functional groups.
[0059] Depend on Figure 1 As shown in Figure (e), GNR is at 1350cm -1 and 1590cm -1 There are two characteristic peaks near the edge of GNR, so most of the edge structure of GNR is armchair-shaped, see Figure 1 At the same time, in Raman spectroscopy characterization, the intensity ratio of the D band to the G band (I D / I G ratio) to estimate the integrity of carbon materials. MWCNTs show obvious G-type, I D / I G The lower the ratio, the higher the structural integrity. When MWCNT is oxidized to GONR, I D / I G The ratio increased from 0.41 to 0.97, indicating that GONR produced edge structures and defects during the oxidation process; after the reduction process, I D / I G The ratios increased to 1.06 (GNR-ChemR) and 1.16 (GNR-ThermR), respectively.
[0060] The following Tuinstra & Koenig equation is used to calculate the distance between defects (L) at a wavelength of 532 nm: a ), the result is as follows Figure 1 As shown in Figure (g).
[0061]
[0062] The distance between defects of MWCNT (L a ) is 46.6nm, and the distance between defects of GONR (L a ) is 19.8nm. After reduction, the distance between defects of GONR (L a ) is further shortened to 18.1nm (GNR-ChemR) and 16.6nm (GNR-ThermR). Compared with the chemically reduced GNR-ChemR, the defect distance (L a ) is smaller, indicating that more in-plane defects are generated on the material surface during thermal reduction, which is beneficial to increase electron dissipation.
[0063] Depend on Figure 1 Figure (f) shows that the weight loss of MWCNT at 900°C accounts for 0.04% of the total weight; after the oxidation process, the degradation temperature of GONR drops to 200°C, and the total weight loss rate is 58.1%, which is due to the introduction of oxygen-containing groups on the edges and planes of GONR during the oxidation reaction; after reduction, the total weight loss rate of GNR-ChemR is 32.8%, and the total weight loss rate of GNR-ThermR is 8.8%. This should be caused by the reduction of the content of oxygen-containing groups in the material after reduction.
[0064] Depend on Figure 1 The XPS results shown in Figures (h) to (k) show that during the oxidation process, the C / O atomic ratio decreased from 99.4 / 0.3 (MWCNT) to 46 / 52 (GONR). After GONR was reduced, the C / O atomic ratio increased to 61.7 / 31.8 (GNR-ChemR) and 90.2 / 6.4 (GNR-ThermR), respectively. That is, it was found that the thermal reduction method can remove the functional groups in GONR better than the chemical reduction method. The GNR-ThermR prepared by the thermal reduction method has better conductivity, which is beneficial to the conduction loss of the nanocomposite material.
[0065] The test data of this example show that there are obvious differences in the composition and in-plane defects of graphene nanoribbons (GNRs) prepared by chemical reduction and thermal reduction.
[0066] Example 3
[0067] In this embodiment, the GNR-ThermR prepared in Example 1 and polyvinylidene fluoride (PVDF) were blended by a solution blending method to prepare a GNR / PVDF nanocomposite material.
[0068] (1) The GNR-ThermR prepared in Example 1 was added to N,N-dimethylformamide (DMF) and ultrasonically dispersed for 4 h to obtain a GNR-ThermR dispersion.
[0069] PVDF was added into DMF and stirred at 80°C until PVDF was completely dissolved to form a PVDF solution with a concentration of 0.2 g / mL.
[0070] (2) GNR-ThermR dispersion and PVDF solution in different proportions were mixed, placed in an open container, and stirred at 90°C for about 3 h until the mixed solution turned into a viscous state. The viscous mixed solution was dried to obtain GNR-ThermR / PVDF nanocomposites with GNR-ThermR contents of 5wt%, 10wt% and 15wt%.
[0071] Comparative Example 2
[0072] In this comparative example, MWCNT and PVDF were blended by solution blending to prepare MWCNT / PVDF nanocomposites. The operation of this comparative example is basically the same as that of Example 3, except that GNR-ThermR was replaced with MWCNT to prepare MWCNT / PVDF nanocomposites with MWCNT contents of 5wt%, 10wt% and 15wt%.
[0073] Comparative Example 3
[0074] In this comparative example, graphene nanosheets (GNP) and PVDF were blended by solution blending to prepare GNP / PVDF nanocomposites. The operation of this comparative example is basically the same as that of Example 3, except that GNR-ThermR is replaced with GNP to prepare GNP / PVDF nanocomposites with GNP contents of 5wt%, 10wt% and 15wt%.
[0075] The nanocomposites prepared in Example 3 and Comparative Examples 2-3 were prepared into different thicknesses, and then the dielectric properties of these nanocomposites in the Ku band (12.4-18 GHz) were characterized using a vector network analyzer and the reflection loss (RL, dB) was calculated. The calculation formula for the reflection loss is as follows:
[0076]
[0077]
[0078] In the formula, Z in is the input impedance of the material, Z 0 is the free space impedance (377Ω), μ r and ε r are the complex permeability and dielectric constant, f and d are the frequency of the electromagnetic wave (Hz) and the thickness of the material (m), and c is the speed of light (m / s).
[0079] Figure 2 The reflection loss of MWCNT / PVDF, GNR-ThermR / PVDF and GNP / PVDF nanocomposites at different nanofiller contents (5wt%, 10wt% and 15wt%) is shown. Figure 2 It can be seen that when the nanofiller content is 10wt%, the GNR-ThermR / PVDF nanocomposite material exhibits the best electromagnetic wave absorption performance, and the reflection loss at 15.9GHz reaches -42.6dB, which is much higher than the -21.8dB of the MWCNT / PVDF nanocomposite material with a nanofiller content of 10wt%, and the -25.6dB of the GNP / PVDF nanocomposite material with a nanofiller content of 10wt%.
[0080] Figure 3 Figures (a) to (c) show the reflection loss and impedance matching of MWCNT / PVDF, GNR-ThermR / PVDF and GNP / PVDF nanocomposites when the nanofiller content is 15wt%.
[0081] Example 4
[0082] In this embodiment, the GNR-ThermR / PVDF nanocomposite material with a nanofiller content of 15 wt% prepared in Example 3 is used as a basis to prepare a GNR-ThermR / PVDF nanocomposite foamed material by supercritical carbon dioxide foaming.
[0083] (1) A GNR-ThermR / PVDF nanocomposite material having a nanofiller content of 15 wt% is hot-pressed at 200° C. to obtain a sheet-like GNR-ThermR / PVDF nanocomposite material formed body.
[0084] (2) placing the molded body prepared in step (1) in an autoclave, introducing carbon dioxide gas as a foaming agent into the autoclave, adjusting the temperature of the autoclave to 121° C. and the pressure to 13.8 MPa to convert the carbon dioxide gas into a supercritical fluid state, maintaining the above temperature and pressure to swell the composite material molded body for 40 minutes, then releasing the pressure to foam, cooling and shaping, and obtaining a GNR-ThermR / PVDF nanocomposite foamed material.
[0085] Comparative Example 4
[0086] In this embodiment, the MWCNT / PVDF nanocomposite material with a nanofiller content of 15 wt % prepared in Comparative Example 2 is used as a basis to prepare a MWCNT / PVDF nanocomposite foamed material by supercritical carbon dioxide foaming.
[0087] The preparation method of the MWCNT / PVDF nanocomposite foam material is basically the same as that of Example 4, except that the GNR-ThermR / PVDF nanocomposite material with a nanofiller content of 15 wt% is replaced by a MWCNT / PVDF nanocomposite material with a nanofiller content of 15 wt%.
[0088] Comparative Example 5
[0089] In this embodiment, the GNP / PVDF nanocomposite material with a nanofiller content of 15 wt % prepared in Comparative Example 3 was used as a basis to prepare a GNP / PVDF nanocomposite foamed material by supercritical carbon dioxide foaming.
[0090] The preparation method of the GNP / PVDF nanocomposite foam material is basically the same as that of Example 4, except that the GNR-ThermR / PVDF nanocomposite material with a nanofiller content of 15 wt% is replaced by a GNP / PVDF nanocomposite material with a nanofiller content of 15 wt%.
[0091] Figure 3 Figures (d) to (f) are scanning electron microscope images of the cross-sections of the MWCNT / PVDF nanocomposite foam material prepared in Comparative Example 4, the GNR-ThermR / PVDF nanocomposite foam material prepared in Example 4, and the GNP / PVDF nanocomposite foam material prepared in Comparative Example 5. As can be seen from the figure, all three nanocomposite foam materials have rich pore structures. The volume percentage (Vf) of the air phase in the MWCNT / PVDF nanocomposite foam material prepared in Comparative Example 4, the GNR-ThermR / PVDF nanocomposite foam material prepared in Example 4, and the GNP / PVDF nanocomposite foam material prepared in Comparative Example 5 were further tested, and the volume percentage (Vf) of the air phase was 20% (MWCNT / PVDF nanocomposite foam material), 22.48% (GNR-ThermR / PVDF nanocomposite material), and 30.07% (GNP / PVDF nanocomposite foam material), respectively.
[0092] The MWCNT / PVDF nanocomposite foam material prepared in Comparative Example 4, the GNR-ThermR / PVDF nanocomposite foam material prepared in Example 4, and the GNP / PVDF nanocomposite foam material prepared in Comparative Example 5 were prepared in different thicknesses, and then the dielectric properties of these nanocomposites in the Ku band (12.4-18 GHz) were characterized using a vector network analyzer to calculate the reflection loss (RL, dB) and impedance match (Z in / Z 0 ), the result is as follows Figure 3 As shown in Figures (a') to (c').
[0093] Figure 3 Figures (a) to (c) show the reflection loss and impedance matching of MWCNT / PVDF, GNR-ThermR / PVDF and GNP / PVDF nanocomposites under the condition of 15wt% nanofiller content, that is, the reflection loss and impedance matching of the reflection loss before foaming. It can be seen from the figure that the unfoamed nanocomposite exhibits poor impedance matching (Z in / Z 0 ), so most of the electromagnetic waves are reflected, and the nanocomposite material exhibits lower electromagnetic wave absorption performance (i.e., reflection loss performance).
[0094] Depend on Figure 3 As shown in Figures (a') to (c'), after the supercritical carbon dioxide foaming process, the GNR-ThermR / PVDF nanocomposite foam material exhibits better impedance matching performance than the MWCNT / PVDF nanocomposite foam material and the GNP / PVDF nanocomposite foam material, and the reflection loss increases to -54.1dB when the frequency of the electromagnetic wave is 16.8GHz. The following effects have a significant impact on the impedance matching and reflection loss of the reinforcement material:
[0095] (1) The introduction of a low-dielectric air phase reduces the dielectric constant of the material and enhances the impedance matching of the material; (2) The nanocomposite foam material has a large number of pores and a large solid-air interface area, which enhances the multiple reflection and scattering properties of the nanocomposite foam material; (3) Compared with MWCNT / PVDF nanocomposite foam materials and GNP / PVDF nanocomposite foam materials, graphene nanoribbons (GNRs) have both lamellar and fibrous structures, which enhance the interface polarization between GNRs and GNRs. In addition, this interface polarization is enhanced during the foaming process due to the stretching of the pore wall, that is, more GNR-GNR interface polarization structures are formed by inducing the orientation of GNRs in the pore wall; (4) The atomic defects constructed on the GNRs by the thermal reduction method of the present invention are also conducive to electron dissipation, which can improve the electromagnetic wave absorption performance of the GNRs. In addition, the thermal reduction method can better remove the functional groups in the GONRs to obtain GNRs with a lower functional group content, which is conducive to improving the conductivity of the GNRs and thereby enhancing the conduction loss of the composite material containing the GNRs.
[0096] Figure 4 Figures (a) to (c) are schematic diagrams of the evolution of filler interface polarization of CNT, GNR and GNP during the pore wall stretching process during foaming in this embodiment. For MWCNT / PVDF nanocomposite foaming materials, due to its rod-like structure, the interface polarization between adjacent MWCNTs is suppressed during the pore wall stretching process due to the point-to-point interface structure. For GNP / PVDF nanocomposite foaming materials, although GNPs exhibit a superior two-dimensional structure, which is conducive to the construction of surface-surface polarization structures in the pore walls, however, during the pore wall stretching process, due to the low aspect ratio of GNPs, adjacent GNPs are easily pulled apart and separated, which is also not conducive to the construction of strong interface polarization structures in the foaming material. Compared with 1D MWCNT and 2D GNP, the long strip-shaped GNR combines the advantages of face-to-face polarization and long aspect ratio. Therefore, the GNR-GNR interface polarization structure will not be adversely affected during the pore wall stretching process, which is conducive to enhancing the absorption of electromagnetic waves.
[0097] Example 6
[0098] In this example, the volume percentage of the air phase in the GNR-ThermR / PVDF nanocomposite foamed material prepared by supercritical carbon dioxide foaming was adjusted by adjusting the temperature of the autoclave in Example 4.
[0099] The operation of this embodiment is basically the same as that of embodiment 4, except that:
[0100] In the first group of experiments, the temperature of the autoclave was adjusted to 118°C to prepare a GNR-ThermR / PVDF nano-composite foam material with an air phase volume percentage (Vf) of 13.79%. In the second group of experiments, the temperature of the autoclave was adjusted to 124°C to prepare a GNR-ThermR / PVDF nano-composite foam material with an air phase volume percentage (Vf) of 35.9%.
[0101] The GNR-ThermR / PVDF nanocomposite foam materials with different air phase volume percentages prepared in the two groups of experiments in this embodiment and the GNR-ThermR / PVDF nanocomposite foam material prepared in Example 4 (air phase volume percentage (Vf) is 22.48%) were prepared into different thicknesses, and the dielectric properties of these nanocomposites in the Ku band (12.4-18 GHz) were characterized by a vector network analyzer, and the reflection loss (RL, dB) and impedance match (Z in / Z 0 ), the result is as follows Figure 5 As shown in Figures (d) to (i), Figure 5 Figures (a) to (c) are schematic diagrams of the GNR-ThermR / PVDF nanocomposite foam material and its wave absorption with the corresponding air phase volume percentage.
[0102] Depend on Figure 5 It can be seen that the impedance matching of GNR-ThermR / PVDF nanocomposite foam material gradually increases with the increase of the volume percentage of the air phase (Vf). This is because the air phase (cellular structure) is introduced into the GNR-ThermR / PVDF nanocomposite material, which increases the impedance matching and makes Z in / Z 0 Close to 1, which is conducive to the electromagnetic wave entering the GNR-ThermR / PVDF nanocomposite foam material and reducing the reflectivity of the electromagnetic wave. For the reflection loss of the GNR-ThermR / PVDF nanocomposite foam material, with the increase of the volume percentage of the air phase (Vf), the absorption performance of electromagnetic waves first increases and then decreases. The enhancement of its electromagnetic wave absorption performance can be attributed to the enhancement of impedance matching, while the decrease in EMW absorption performance can be attributed to the excessive stretching of the pore wall, which causes the connection of GNR-ThermR in the pore wall to be disconnected, so the interface polarization effect is reduced.
Claims
1. A graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance, characterized in that: The nanocomposite foaming material is composed of a polymer matrix material, a graphene nanoribbon and an air phase, wherein the graphene nanoribbon has atomic defects, the air phase is distributed in the polymer matrix material to form pores with a closed-cell structure, and the graphene nanoribbon is distributed in the pore wall to form a graphene nanoribbon-graphene nanoribbon interface polarization structure; in the nanocomposite foaming material, the mass content of the graphene nanoribbon is 15wt% to 20wt%, and the volume percentage of the air phase is 20% to 30%; the polymer matrix material is polyvinylidene fluoride; The carbon-oxygen atomic ratio of graphene nanoribbons is (12-15):1, the distance between defects in graphene nanoribbons is 16-17 nm, and the I D / I G The ratio is 1.1 to 1.2; the I D / I G The ratio refers to the intensity ratio of the D band to the G band in the Raman spectrum of the graphene nanoribbon; the inter-defect distance of the graphene nanoribbon refers to the inter-defect distance at a wavelength of 532 nm calculated by the Tuinstra & Koenig equation shown in formula (I), In formula (I), L a is the distance between defects, λ=532nm, is the intensity ratio of D band to G band in the Raman spectrum of graphene nanoribbons; The method for preparing the graphene nanoribbon comprises the following steps: (1) dispersing carbon nanotubes in a sulfuric acid-phosphoric acid mixed acid, stirring for 1 to 2 hours under ice bath conditions, adding potassium permanganate, then heating to 60 to 70° C., stirring and reacting for 2 to 4 hours, cooling the resulting reaction solution to room temperature and pouring it into ice water containing hydrogen peroxide, leaving it to stand for 20 to 30 hours, discarding the supernatant, and dialyzing the resulting reaction slurry with deionized water until the pH value of the reaction slurry is 6 to 7, thereby obtaining graphene oxide nanoribbons; In the sulfuric acid-phosphoric acid mixed acid, the volume ratio of sulfuric acid to phosphoric acid is (8.5-9.5):1; the usage ratio of carbon nanotubes to sulfuric acid-phosphoric acid mixed acid is 150-250 mL of sulfuric acid-phosphoric acid mixed acid per 1 g of carbon nanotubes; the usage of potassium permanganate is 5-6 times the mass of the carbon nanotubes; (2) reacting the graphene oxide nanoribbon obtained in step (1) at 900-950° C. in an inert gas atmosphere for 1.5-2 h to obtain graphene nanoribbon.
2. The graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance according to claim 1, characterized in that: In step (2), the temperature is raised from room temperature to 900-950° C. at a heating rate of 4-6° C. / min in an inert gas atmosphere, and kept at 900-950° C. for 1.5-2 h to obtain graphene nanoribbons.
3. The graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance according to claim 1, characterized in that: In the ice water containing hydrogen peroxide in step (1), the volume percentage of hydrogen peroxide is 5% to 10%, and the temperature of the ice water containing hydrogen peroxide is 0 to 4°C.
4. The method for preparing the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) preparing a graphene nanoribbon / polymer nanocomposite material by a solution blending method, and hot-pressing the obtained graphene nanoribbon / polymer nanocomposite material to obtain a composite material formed body; (2) using a supercritical fluid to swell the composite material formed body and release the pressure to foam to obtain a nano-composite foam material, during the cell growth process, the cell wall is subjected to a two-dimensional stretching effect, the graphene nanoribbons are oriented in the cell wall and form a graphene nanoribbon-graphene nanoribbon interface polarization structure; in this step, the swelling and foaming conditions are controlled so that the volume percentage of the air phase in the nano-composite foam material is 20% to 30%.
5. The method for preparing the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance according to claim 4, characterized in that: The method of using supercritical fluid to swell a composite material molded body and release pressure for foaming is as follows: placing the composite material molded body in a high-pressure cavity, introducing a gas as a foaming agent into the high-pressure cavity, adjusting the temperature and pressure of the high-pressure cavity to convert the gas as a foaming agent into a supercritical fluid state, maintaining the aforementioned temperature and pressure to swell the composite material molded body, then releasing pressure for foaming, cooling and shaping, and obtaining a nano-composite foamed material.
6. The method for preparing the graphene nanoribbon nanocomposite foam material with excellent wave absorbing performance according to claim 5, characterized in that: The gas introduced into the high-pressure chamber as a foaming agent is CO2 or N2.
Citation Information
Patent Citations
Preparation method of highly-dispersed graphene oxide nanobelt liquid
CN104817075A
Preparation method of graphene nanobelt / PMMA microcellular foam nanocomposite
CN106566156A